Նորահայտ մետաղե արձանագիր խաչեր Եղեգիսից - Արսեն Մարտիրոսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Автор доклада анализирует два металлических креста с села Ехегиса Республики Армения, которые были подарены монастырю Святого Карапета и предназначались для спасения душ тех людей, имена которых мы можем увидеть на их обратной стороне благодаря дарственным надписям. The author of the report analyzes two metal crosses from the village of Yeghegis located in the Republic of Armenia. These crosses were donated to St. Karapet Monastery and were intended for the salvation of the souls of those people whose names, thanks to dedicatory inscriptions, we can see on the reverse side of the cross.
Keywords: History; Fine Arts; Sepulchral Monuments